The Role of Play-Based Digital Storytelling in Enhancing Social-Emotional Competencies in Preschool Children - Zetira Ahmad (Indonesian Journal of Multidisciplinary Scientific Studies, 2026)
This study explores the impact of play-based digital storytelling on the social-emotional development of children aged 4-5 years. In an increasingly digital world, the integration of technology in Early Childhood Education (ECE) remains a subject of debate. This research utilized a mixed-methods approach, observing 40 preschool children over an eight-week intervention period. Results indicate that when digital storytelling is integrated with collaborative play, children demonstrate significant improvements in empathy, turn-taking, and emotional regulation. The findings suggest that digital tools, when used as a medium for collaborative creation rather than passive consumption, can be a powerful catalyst for social-emotional growth. This study challenges the conventional digital isolation narrative by proving that shared digital interfaces can serve as powerful social mediators when implemented through structured, peer-oriented frameworks.